اتجاهات الآباء نحو لعب الأبناء وعلاقتها بعض المتغيرات الديموغرافية - هوادف, رابح; فارس, علي (جامعة الوادي - University of Eloued, 2023)
تهدف الدراسة الحالية إلى الكشف عن طبيعة اتجاهات الآباء نحو لعب الأبناء في ضوء بعض المتغيرات، وقد تكونت عينة الدراسة من (120) والداً ووالدة، والتي اختيرت بأسلوب المعاينة غير العشوائية بالطريقة العرضية. ولجمع البيانات تم استخدام مقياس الاتجاهات نحو اللعب الذي صممه نظمي أبو مصطفى وعطاف أبو غالي (2005). ولمعالجة هذه البيانات بعد التفريغ تم استخدام الإحصاء الوصفي والاستدلالي من خلال الاستعانة ببرنامج الحزمة الإحصائية للعلوم الاجتماعية وبعد المعالجة الإحصائية للبيانات المجمعة أسفرت الدراسة إلى أنه يمتلك الآباء اتجاهات ايجابية نحو لعب أبنائهم. كما توجد فروق في مستوى اتجاهات الآباء نحو لعب الأبناء تبعاً لمتغير جنس الوالدين لصالح الأمهات، وتبعاً لمتغير المستوى الاجتماعي للوالدين لصالح ذوي المستوى الاجتماعي المرتفع. وتبعاً لمتغير المستوى التعليمي للوالدين لصالح ذوي المستوى التعليمي المرتفع. Abstract : The present study aims at revealing the nature of parents' attitudes towards children's playing and its relationship with some variables. The study sample consisted of (120) fathers and mothers, which were selected by random sampling method. To collect data, used Parent's attitudes towards children's playing scale which designed by Nazmi Abu Mustafa and Ataf Abu Ghali (2005). In order to process this data after discharge, descriptive and indicative statistics were used by using the SPSS (v. 20) program. After the statistical analysis, the current study showed the following results: Parents have positive attitudes towards their children's playing. There are differences in the level of parents' attitudes towards children's playing according to the gender variable parents in favor of mothers. There are differences in the level of parents' attitudes towards children's playing according to the variable level of social parents in favor of the high social level. There are differences in the level of parents' attitudes towards children's playing according to the variable educational level of parents in favor of those with higher education level.
مقال
Keywords: اتجاهات الآباء ؛ لعب الأبناء ؛ متغيرات ديموغرافية; parents' attitudes ; children's playing ; demographic Variables